A tin oxide/silicon heterojunction with a nano litchi shell structure for ultrafast, high-detectivity, self-powered broadband photodetectors. Issue 6 (19th January 2022) - Ling, Cuicui; Feng, Bingxin; Wang, Xiaomeng; Zhang, Lingtan; Zhang, Tuo; Cao, Min; Yu, Daoyong; Xue, Xin; Xue, Qingzhong; Zhang, Jianqiang; Wang, Chuanke; Zhu, Lei; et al.
Abstract : We develop an ultrafast, high-detectivity, self-powered broadband PD based on SnO2 nano litchi shell structure/n-Si heterojunction. The excellent performance attributed to the SnO2 nano litchi shell structure, and meaningful interface barrier. Abstract : Self-powered photodetectors with excellent figures-of-merit, fast response speed, and broadband detection capability have drawn tremendous research interest. However, it is still challenging to develop excellent light-absorbing materials as photodetectors with effective separation of carriers. In this paper, we develop a SnO2 nano litchi shell structure/n-Si heterojunction with enhanced broadband light absorption for self-powered photodetection. The advantageous photoresponse performance of the SnO2 nano litchi shell structure/n-Si heterojunction is attributed to the following factors: (1) the SnO2 nano litchi shell structure has a large specific surface area to trap light; (2) the spherical cavity structure increases the light utilization rate by scattering and multiple reflections; (3) the significant Fermi energy difference at the junction of the SnO2 layer and Si layer. As a result, the device exhibits a broadband detection capacity from ultraviolet (365 nm) to near-infrared (980 nm) at 0 voltage. Under 900 nm (10 μW cm −2 ), the photodetector shows the responsivity of 0.033 A W −1, the photosensitivity of 8.35 × 10 8 cm 2 W −1, the detectivity of 2.94 × 10 12 Jones, the response time of 20.8 μs, and the recovery time of 285 μs. We also evaluated the near-infrared low signal imaging and fluorescence detection capability of the device. We expect that the SnO2 nano litchi shell structure/n-Si heterojunction photodetector will have great potential in biomedical and environmental monitoring, and military reconnaissance.